2021
DOI: 10.1002/adem.202100968
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Heating Neutron and X‐Ray Diffraction Analyses for Revealing Structural Evolution during Postprinting Treatments of Additive‐Manufactured 316L Stainless Steel

Abstract: Herein, lab‐scale X‐ray diffraction and in situ heating neutron diffraction analyses for evaluating the structural changes at postprinting nanostructuring and structural relaxation upon heating, respectively, in an additive‐manufactured (AM) 316L stainless steel are conducted. The nanostructured AM steel after nanostructuring by high‐pressure torsion reached crystallite sizes of 23–26 nm, a dislocation density of ≈45 × 1014 m−2 and a microstrain of >0.008. A limited amount of deformation‐induced ε‐martensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 68 publications
2
16
1
Order By: Relevance
“…53) It should be noted that the stainless steel was manufactured by an additive manufacturing (AM) approach using a laser powder bed fusion (L-PBF) technique, and the initial as-built sample had a subgrain size of 300 nm within several tens of micron-sized grains. 48) A measurement by transmission electron microscopy (TEM) revealed that the microstructure of the AM 316L steel disks achieved an average grain size of 60 nm in the equiaxed shape after 8 and higher HPT turns, 45,48) which is consistent with earlier reports on the HPT-processed 316L-grade SS regardless of manufactured conventionally by casting 54,55) or through AM. 56) The aforementioned microstructure changes, such as nanostructuring, in bulk metals during HPT can be systematically examined ex-situ using a series of separate XRD measurements.…”
Section: General Observations After Spd: Hardness and Structural Changessupporting
confidence: 88%
See 1 more Smart Citation
“…53) It should be noted that the stainless steel was manufactured by an additive manufacturing (AM) approach using a laser powder bed fusion (L-PBF) technique, and the initial as-built sample had a subgrain size of 300 nm within several tens of micron-sized grains. 48) A measurement by transmission electron microscopy (TEM) revealed that the microstructure of the AM 316L steel disks achieved an average grain size of 60 nm in the equiaxed shape after 8 and higher HPT turns, 45,48) which is consistent with earlier reports on the HPT-processed 316L-grade SS regardless of manufactured conventionally by casting 54,55) or through AM. 56) The aforementioned microstructure changes, such as nanostructuring, in bulk metals during HPT can be systematically examined ex-situ using a series of separate XRD measurements.…”
Section: General Observations After Spd: Hardness and Structural Changessupporting
confidence: 88%
“…In general, these fundamental features of microstructure and mechanical properties for the HPT-processed metals are often examined and measured ex-situ through the combination of the Vickers microhardness tests, optical and electron microscopy, and lab-scale XRD. Figure 1 shows (a) the Vickers microhardness evolution across the steel disk diameter with increasing numbers of HPT rotations through 8 turns, 45,48) and (b) the hardness change of the steel against shear strain, £, introduced by HPT through 15 turns, which is given by…”
Section: General Observations After Spd: Hardness and Structural Changesmentioning
confidence: 99%
“…A very similar neutron study as on the present CoCrFeNi HEA has been published by Kawasaki et al on 316 L Stainless Steel. [ 72 ] Therein, Figure 6b of reference, [ 72 ] also a systematic strain offset can be recognized between the heating and the cooling curves, about 5× smaller than the present results for HEA. Such scaling can be explained by the fact that thermal vacancy creation is 5× larger in an equiatomic four‐species HEA as compared to a (near) monoatomic alloy.…”
Section: The Processing–microstructure–property Paradigmcontrasting
confidence: 47%
“…As a conventional Williamson-Hall analysis, plotting peak width against peak location behaves unsystematic, the modified Williamson Hall method taking into account the anisotropic strain fields around dislocations, has been applied for obtaining reliable values of dislocation densities [30]. Very similar studies have been reported by the same group [34] on high-pressure torsion processed stainless steel. Both materials show consistently equivalent microstructural behavior on heating, correlating the different temperature regimes with hardness after annealing, revealing that hardness reaches a maximum after recovery, just before recrystallization.…”
Section: Materials After Severe Plastic Deformationmentioning
confidence: 89%